Bridging The Gap Between Basic Financial Accounting Knowledge In High School And Higher Education (College) - Elizabeth Tiur Manurung; Felisia Felisia; Puji Astuti Rahayu; Monica Paramita R. Putri Dewanti; Arthur Purboyo (Universitas Islam Bandung, 2022)
From observing the phenomenon of the gap between basic financial accounting learning materials in the middle-high level of education and high level of education, the team of lecturers from the accounting study program have been motivated as follows: Unpar seeks to equalize the knowledge of the two educational strata by using sharing method. The aim is to bridge the gap in accounting material in high school with basic financial accounting material in collegeThis research with analytical descriptive method uses a sample of high school teachers who are willing to participate in this sharing program through a webinar with a zoom meeting platform held in 2020 and 2021. The activity was attended by 14 SMA and SMK with eighteen teachers and one hundred and twenty eight students. Materials regarding adjustment journals and plant and intangible assets have been taught according to the teacher's request. The material is presented in the form of a two-way discussion so that the facilitator and participants can discuss in depth, while the activity for students is an introduction to the accounting profession.The knowledge enrichment of accounting material related to today's business practices that can be applied in teaching and learning activities in high school is recognized by the teachers as very useful and accompanied with high enthusiasm during the sharing. In turn, their high school graduates understand this material better and can take the same courses in college better. This will form the building of accounting knowledge in students in the future.